THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN DRIVING MOTIVATION AND IMPROVING ORGANIZATIONAL PERFORMANCE - Sandi Nurhakim (Journal Informatic, Education and Management (JIEM), 2026)
Transformational leadership is a leadership style that focuses on a leader’s ability to inspire, motivate, and encourage positive change among organizational members. This study aims to examine the influence of transformational leadership on improving motivation and organizational performance. The research uses a qualitative approach through literature review methods derived from journals, books, and relevant scientific articles. The findings indicate that transformational leadership plays an important role in creating a productive work environment, increasing member loyalty, and fostering higher work enthusiasm. In addition, transformational leaders are able to provide a clear vision, establish good communication, and become role models for organizational members. Therefore, transformational leadership can be considered an effective strategy for improving the quality of human resources and organizational success.